The Effectiveness of Proving Collateral Status on Differences in Murabahah Dispute Verdicts in Religious Courts - Nuraida, Tasya (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2025)
The research aims to assess the extent to which the strength or weakness of collateral evidence affects the consideration and direction of the judge's decision, as well as how the quality of evidence contributes to the realization of justice and legal certainty. The research uses a normative juridical method with a case study approach to four decisions of the Religious Court in Sleman and Gunungkidul. The analysis is carried out through legal interpretation, doctrinal analysis, and comparative jurisprudence. The results of the study show that when the collateral is proven to be legally valid and supported by authentic documents, the judge tends to grant the execution request in full. On the other hand, if the collateral evidence is weak or has a formal defect, the judge only grants part of the claim or directs the parties to mediate in an effort to achieve substantive justice. The conclusion of the study emphasizes that the effectiveness of proof is a direct indicator of the effectiveness of the law in the practice of sharia economic justice. Strengthening evidence not only improves the legal position of Islamic financial institutions, but also maintains public trust in the sharia-based financial system. Theoretically, this study integrates the theory of proof, legal certainty, and legal effectiveness; Practically, the study recommends standardization of evidentiary procedures and the preparation of consistent jurisprudential guidelines in the assessment of collateral in murabahah cases.